x(-b)=m(x-c)
the answer is: (y-b)/x = m y = mx + b y - b = mx (y-b)/x = m
To multiply m x 10a by n x 10b: multiply the numbers (m x n) add the powers (a + b) (m x 10a) x (n x 10b) = mn x 10a+b To divide m x 10a by n x 10b: divide the numbers (m / n) subtract the powers (a - b) (m x 10a) / (n x 10b) = m/n x 10a-b
x = (y-b)/m
y-b/x=m
Not quite. 'm' is the slope of the line. 'b' is the y-intercept The x-intercept is ( -b/m ).
y = mx + b y - b = mx (y - b) / x = m (m is the slope, except where x = 0)
Y=mx+b. first you subtract b from both sides of the equation. Y-b=mx then you divide m from both sides because x is being multiplied by m. so then you get (y-b)/m=x and that's your answer
y=m(x)+b
y = mx + bAt the x-intercept, y = 0 :0 = mx + bSubtract b from each side of the equation :-b = mxDivide each side by 'm' :-b/m = x
echo Enter two numbers with space in between read a b m=$a if [ $b -lt $m ] then m=$b fi while [ $m -ne 0 ] do x=`expr $a % $m` y=`expr $b % $m` if [ $x -eq 0 -a $y -eq 0 ] then echo gcd of $a and $b is $m break fi m=`expr $m - 1`
a) 6.4 x 10^6 m b) 5.48 x 10^-5 s